Selection of DNA aptamers against Chikungunya virus Envelope 2 Protein and their application in sandwich ELASA - Anna, Andrew; Magdline Sia, Henry Sum; Ch'ng, Ewe Seng; Tang, Thean Hock; Citartan, Marimuthu (Elsevier B.V., 2025)
Chikungunya fever, caused by Chikungunya virus (CHIKV) exhibits clinical features that mimic that of other arbovirus infections such as dengue. CHIKV Envelope 2 (E2) protein, an antigenic epitope of CHIKV, has been identified as an ideal marker for diagnostics. The current CHIKV antigen detection tests are largely based on antibodies but are beleaguered by issues such as sensitivity to high temperature, expensive and prone to batch-tobatch variations. Aptamers are suitable alternatives to antibodies as they are cheaper and have no batch-to-batch variations compared to antibodies. In this study, DNA aptamer selection against CHIKV E2 proteins was performed using two different randomized ssDNA libraries. Chik-2 (96-mer) and Chik-3 (76-mer) were isolated from these two libraries and were identified as the potential aptamers against CHIKV E2 protein. The binding affinity of Chik-2 and Chik-3 against CHIKV E2 protein was estimated at 177.5 ± 32.69 nM and 30.01 ± 3.60 nM, respectively. A sandwich ELASA was developed, and this assay showed a detection limit of 2.17 x 103 PFU/mL. The sensitivity and specificity of the assay were 80 % and 100 %, respectively. The assay showed no crossreactivity with dengue-positive samples, demonstrating the enormous diagnostic potential of these aptamers for the detection of CHIKV.